Implementation Joyful Learning Total Physical Response (TPR)-Based to Elementary School English Teachers in Dumai - Erni, Erni; Azhar, Fadly; Jismulatif; Dahnilsyah; Harfal, Zaldi (LingPoet: Journal of Linguistics and Literary Research, 2024)
Based on the Independent curriculum, English is taught at elementary schools from first grade until sixth grade, which requires Elementary school teachers' innovation to improve their competencies in English learning. This descriptive study aimed to show elementary school teachers' perception toward the implementation of Joyful Learning TPR-Based with contextual media and the portrait of their profiles. Observation and questionnaires were used as the research instrument. Forty-six elementary school teachers were involved as the participants of the study. It is concluded that the teacher's perception toward implementing the Joyful Learning TPR-Base was positive, and they were interested in using the Joyful Learning TPR-Based in their English class. Training relevant to teachers' needs was needed.